Underground: Hacking, madness and obsession on the electronic frontier - Dreyfus, Suelette; Assange, Julian, 1971- (Salt Lake City, UT : Project Gutenberg, 2003)
"Underground: Hacking, madness and obsession on the electronic frontier" by Suelette Dreyfus is a book published in 1997. It chronicles the exploits of Australian, American, and British black hat hackers during the late 1980s and early 1990s. The book follows notorious figures who penetrated secure networks, evaded law enforcement, and became pioneers of computer crime. Among them is Julian Assange, who researched the book and appears as the hacker "Mendax." Their stories reveal an underground world of obsession and digital rebellion. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Underground_(Dreyfus_book)
Release date is 2003-11-01
Keywords: Computer hackers -- Australia -- Biography; Computer crimes -- Australia; Computer security -- Australia